2014
DOI: 10.1007/s10551-014-2268-7
|View full text |Cite
|
Sign up to set email alerts
|

Being Good When Being International in an Emerging Economy: The Case of China

Abstract: The importance imposed on corporate social responsibility (CSR) is greater in developed economies than in emerging markets. The pressures from various stakeholder groups on the CSR are expected to have substantial spillover impact on companies domiciled in emerging economies that obtain revenues from companies in developed economies. Based on the data from 1,330 listed companies in China, the largest emerging economy in the world, this study provides evidence that the CSR performance of China firms is positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 47 publications
5
84
0
1
Order By: Relevance
“…Given that EMFs suffer from LOE, by communicating CSR activities, EMFs intend to enhance their legitimate image and hence overcome LOE barriers. The findings of this study are in corroboration with extant studies, in which a positive association was found between CSR and firms' internationalization (Cheung et al 2015;Marano et al 2016).…”
Section: Insert Table 2 About Here ---------------------------------supporting
confidence: 91%
“…Given that EMFs suffer from LOE, by communicating CSR activities, EMFs intend to enhance their legitimate image and hence overcome LOE barriers. The findings of this study are in corroboration with extant studies, in which a positive association was found between CSR and firms' internationalization (Cheung et al 2015;Marano et al 2016).…”
Section: Insert Table 2 About Here ---------------------------------supporting
confidence: 91%
“…This issue is important given the quite recent introduction of foreign owners into listed companies on the Chinese mainland. Cheung et al (2014a) report that Chinese firms' CSR A C C E P T E D M A N U S C R I P T…”
Section: H2 Csr Ratings Are Increasing In Firms With Greater Board Gmentioning
confidence: 99%
“…In conclusion, this study provides an initial step in determining the changes in the values that drive work behavior in China, a country that is central to world commerce (Cheung et al, ). Additionally, this study provides a foundation on which subsequent research on Chinese work values evolution may build.…”
Section: Resultsmentioning
confidence: 99%
“…Both regions decreased significantly across this decade, such that by 2010 the businesspeople in the two regions had similar values on the desire to manipulate social power for the sake of achieving personal objectives within the business world (Corzine et al, ). This might be a result of market‐oriented modernization leading to a stronger commitment to structure and formal rules, with an emphasis on more ethical conduct in the workplace and less reliance on personal, guanxi, relationship influences (Cheung, Kong, Tan, & Wang, ).…”
Section: Discussionmentioning
confidence: 99%